Reading Anxiety and Reading Comprehension Skills of Learners of Turkish as a Foreign Language - Hatice Altunkaya; İlhan Erdem (Sakarya University Journal of Education)
The purposes of this study are to reveal the relationship between reading anxiety and comprehension skills of learners of Turkish as a foreign language. In accordance with this goal, who are learning Turkish as a foreign language at B level, were enrolled in the sample. To collect data, “Reading Anxiety Scale” and “Comprehension Achievement Test” were developed for the students learning Turkish as a foreign language at B level. According to the results obtained from the whole of the scale, it was found that the students learning Turkish as a foreign language at B level got on average 46,92 in comprehension anxiety. It was found that the relationship between the scores, the students got at Comprehension Test and the ones they got from Comprehension Anxiety Test and its all subscales, were negative with between -,069 -,275, and that there was not a significant relationship between only in the "comprehension anxiety" subscale of Reading Anxiety Scale and comprehension achievement test scores, and that there was significant difference in other correlation coefficients. In the light of all these results, it was found that there is an inverse correlation between the scores got from comprehension achievement test and the ones got from reading anxiety scale, and that the achievement score obtained from comprehension test decreased as the reading anxiety increased.